Korean Government's response to COVID-19: role of Ministry of Food and Drug Safety (MFDS). (1st October 2020) - Shin, Insoo; Ju, Seon Tae
ABSTRACT: The purpose of this article is to introduce MFDS risk management system and to summarize a series of administrative actions taken during COVID-19. The action covers facilitation of production of personal protective equipment(PPE) including masks and hand sanitizer and their rapid transparent supply, emergency use approval of diagnostic testing kit. MFDS is also in charge of clinical trial approval of therapeutics and vaccine candidates to accelerate the development of vaccines to protect people against COVID-19. At the end, we attempt to assess our COVID-19 management strategies and to suggest future directions in terms of risk management and public communication.